Biopolymer Geogrids for Geotechnics - Oliveira, Gabriel; Falorca, Isabel (KnE Materials Science, 2022)
This study focused on the mechanical characterisation of 3D printed biopolymer geogrids for civil and geotechnical engineering applications. The polylactic acid specimens were designed based on first-order similitude conditions and were produced by fused deposition modelling techniques. An experimental programme was carried out to investigate the mechanical behaviour of 1:2 scale model geogrids undergoing tensile loading conditions, in order to explore their use in soil reinforcement and stabilisation of geomaterials. The secant stiffness at 2.0% of strain and the ultimate tensile strength were used for this purpose. The results showed an average tensile strength of 4.5 ± 0.5 kN/m, which is in good agreement with that of fossil oil-derived polymer prototypes, while presenting a significantly lower elongation at failure. The printing process appeared stable and replicable. The influence of degradation on the tensile properties of 3D printed polylactic acid geogrids over time still needs to be studied. Keywords: geogrid, additive manufacturing, biopolymer, tensile strength, geotechnics